EKRANISASI NOVEL RONGGENG DUKUH PARUK KARYA AHMAD TOHARI KE FILM SANG PENARI KARYA IFA ISFANSYAH - Ratnasari, Andaru; Hafid, Moh; Junal (Buana Bastra, 2025)
This study describes the ecranization process in the novel Ronggeng Dukuh Paruk into the film Sang Penari. The aim is to explain three things: (1) the process of reduction/reduction, (2) the process of addition, and (3) the process of variation. The research method is descriptive qualitative. The research data consist of excerpts from events, characters and characterizations, settings, and plots in the novel Ronggeng Dukuh Paruk and the film Sang Penari. The results show that the ecranization process tends to be more dominant in the reduction aspect compared to the addition and variation aspects. However, the content of the novel's story remains intact and conveyed in the film.